Divide the sum of -2/3 and 3/5 by their product.
Answers
Step-by-step explanation:
sum = -2/3+3/5 = -10+9/15= -1/15
product = -2/3 × 3/5 = -6/15
now divide,
-6/15 × 15/-1
6 answer
Answer:
1/6
Step-by-step explanation:
Sum of -2/3 and 3/5:
=> -2/3 + 3/5
=> (-2/3)*(5/5) + (3/5)(3/3) (3 and 5's LCM is 15. Multiply both the numerator and denominator with the numbers that will equate the denominators to their LCM)\
=> -10/15 + 9/15
=> (-10 + 9)/15 => -1/15 is the sum.
Product of -2/3 and 3/5:
=> (-2/3)*(3/5)
=> (-2*3)(3*5) => -2/5 is the product.
Now, acc. to ques, we have to divide the sum of -2/3 and 3/5 by their product.
=> Sum ÷ Product
=> (-1/15) ÷ (-2/5)
=> (-1/15)(-5/2) (Dividing by a number is the same as by its reciprocal)
=> (-1*{-5})(15*2)
=> 5/30 => 1/6 is the answer. (Minus and minus combine in mutiplication to become plus.)